The Platform Messaging Effect (PME): A quantification of how go-vote reminders on social media platforms can influence voting intentions - Robert Epstein; Amanda Newland; Li Yu Tang; Alyssa Edmison (PLoS ONE, 2026)
Over the past decade, researchers have identified and quantified about a dozen new forms of influence made possible by the internet. Although experts have expressed concern about how users may be harmed by social media content, few studies have sought to quantify the extent to which go-vote reminders on such platforms can impact voting. In the present study, we sent go-vote reminders to US voters on a simulation of Facebook and found (a) that interspersing vote reminders in the message feed significantly increased the magnitude of voting intentions (by over 40% under certain conditions) and (b) that vote reminders also had a significant impact on how people might vote. Because reminders of this sort are ephemeral, social media platforms that send vote reminders to users in a partisan fashion might be able to shift the outcomes of close elections without people’s knowledge.